O2 Carrier Myoglobin Also Exhibits β-Lactamase Activity That Is Regulated by the Heme Coordination State - Shuai Tang; Ai-Qun Pan; Xiao-Juan Wang; Shu-Qin Gao; Xiang-Shi Tan; Ying-Wu Lin (Molecules, 2022)
Heme proteins perform a variety of biological functions and also play significant roles in the field of bio-catalysis. The β-lactamase activity of heme proteins has rarely been reported. Herein, we found, for the first time, that myoglobin (Mb), an O2 carrier, also exhibits novel β-lactamase activity by catalyzing the hydrolysis of ampicillin. The catalytic proficiency ((kcat/KM)/kuncat) was determined to be 6.25 × 1010, which is much higher than the proficiency reported for designed metalloenzymes, although it is lower than that of natural β-lactamases. Moreover, we found that this activity could be regulated by an engineered disulfide bond, such as Cys46-Cys61 in F46C/L61C Mb or by the addition of imidazole to directly coordinate to the heme center. These results indicate that the heme active site is responsible for the β-lactamase activity of Mb. Therefore, the study suggests the potential of heme proteins acting as β-lactamases, which broadens the diversity of their catalytic functions.